THE EFFECT OF INFLATION ON ENTREPRENEURIAL DEVELOPMENT IN EBONYI STATE, NIGERIA (IJOVTECH, 2026)
Over many years, the business environment has seen a steady increase in the prevalence of entrepreneurship. It may benefit national economies and is frequently considered one of the most important engines of economic growth and the creation of employment opportunities. It is, therefore, essential for the government and policymakers to understand the potential reasons for the diversity in the development of new businesses to assist them in adopting policies that are acceptable to support the creation and development of new businesses. Recent years have impacted entrepreneurship development due to Nigeria's unstable economic reality, characterized by financial crises. Thus, this paper investigated the effect of inflation on entrepreneurial development among youths in Ebonyi State, Nigeria. A convenience sample of three hundred and twenty-two undergraduates pooled from three tertiary institutions in the state participated in the study. The study result indicates that the assumption that the inflation would significantly and positively predict entrepreneurial development in Ebonyi State was confirmed at β = .169, p< .05. Thus, the R2 indicated that the increasing inflation in the country contributes about 23.8% variation in entrepreneurial development in Ebonyi State, Nigeria. The study has implications for the development of entrepreneurship in Nigeria.